2023
DOI: 10.1038/s41419-023-05868-z
|View full text |Cite
|
Sign up to set email alerts
|

HNF4A-BAP31-VDAC1 axis synchronously regulates cell proliferation and ferroptosis in gastric cancer

Qingqing Zhou,
Tengfei Liu,
Wenjing Qian
et al.

Abstract: B cell receptor associated protein 31 (BAP31) is closely associated with tumor progression, while the role and mechanism of BAP31 in gastric cancer (GC) remains unknown. This study explored that BAP31 was upregulated in GC tissues and high expression indicated poor survival of GC patients. BAP31 knockdown inhibited cell growth and induced G1/S arrest. Moreover, BAP31 attenuation increased the lipid peroxidation level of the membrane and facilitated cellular ferroptosis. Mechanistically, BAP31 regulated cell pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Prior research has unveiled the intricate involvement of ferroptosis in GC, linking it to cell proliferation, metastasis, and chemotherapy resistance. Key genes and non‐coding RNAs, such as BAP31, [ 30 ] GPX4, [ 31 ] STAT3, [ 32 ] ATF2, [ 33 ] and ARF6, [ 34 ] play pivotal roles in orchestrating ferroptosis in GC, shedding light on its significant contribution to GC development and providing novel avenues for therapeutic exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has unveiled the intricate involvement of ferroptosis in GC, linking it to cell proliferation, metastasis, and chemotherapy resistance. Key genes and non‐coding RNAs, such as BAP31, [ 30 ] GPX4, [ 31 ] STAT3, [ 32 ] ATF2, [ 33 ] and ARF6, [ 34 ] play pivotal roles in orchestrating ferroptosis in GC, shedding light on its significant contribution to GC development and providing novel avenues for therapeutic exploration.…”
Section: Discussionmentioning
confidence: 99%
“…ASCL1 can promote progression of castration-resistant prostate cancer to neurosecretory prostate cancer by mediating ferroptosis resistance [ 58 ]. In gastric cancer cells, the HNF4A-BAP31-VDAC1 axis synchronously regulates tumor cell proliferation and ferroptosis [ 59 ]. The occurrence of ferroptosis is regulated by several genes, such as GPX4, CDKN1A, SLC1A5, and ACSL4, etc.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that DCLK3 has the potential to be a valuable prognostic marker in GC patients 120 . It has been reported that B‐cell receptor‐associated protein 31 (BAP31), through its interaction with Voltage‐Dependent Anion Channel 1 (VDAC1), regulates ferroptosis 121 . Furthermore, FSP1, CDGSH iron sulfur domain 1 (CISD1), and microsomal glutathione S‐transferase 1 (MGST1) have been identified as key suppressors of ferroptosis in GC 122 .…”
Section: Ferroptosis In Gcmentioning
confidence: 99%
“…120 It has been reported that Bcell receptor-associated protein 31 (BAP31), through its interaction with Voltage-Dependent Anion Channel 1 (VDAC1), regulates ferroptosis. 121 Furthermore, FSP1, CDGSH iron sulfur domain 1 (CISD1), and microsomal glutathione S-transferase 1 (MGST1) have been identified as key suppressors of ferroptosis in GC. 122 MGST1, in particular, exhibits notable upregulation in GC and promotes the progression of GC while inhibiting ferroptosis, indicating its potential as a standalone prognostic factor.…”
Section: Prognostic and Diagnostic Markers Associated With Ferroptosi...mentioning
confidence: 99%